2001
DOI: 10.1021/jp010838o
|View full text |Cite
|
Sign up to set email alerts
|

Amino−Imino Tautomerism in Derivatives of Cytosine:  Effect on Hydrogen-Bonding and Stacking Properties

Abstract: The tautomeric preferences of cytosine and its derivatives substituted at position 5 (R ) CH 3 , propynyl, Cl, and Br) have been analyzed both in the gas phase and in aqueous solution by using a combination of stateof-the-art theoretical methods. It is found that 5-substitutions do not alter dramatically the tautomeric preferences of cytosine in gas phase or aqueous solution. The Hoogsteen-type hydrogen-bonding and stacking properties of the imino form of cytosine and its substituted derivatives are examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…The approximate agreement of the long‐time offsets is consistent with approximately equal deposition of pump energy into the water by two‐photon absorption, as expected for these equal‐absorbance solutions. A computational study has shown that 5‐methylation of Cyt does not alter the tautomeric distribution in the gas phase or in solution (29), suggesting once again that ribosyl substitution increases the electronic transition moment of the S 1 → S N transition.…”
Section: Resultsmentioning
confidence: 99%
“…The approximate agreement of the long‐time offsets is consistent with approximately equal deposition of pump energy into the water by two‐photon absorption, as expected for these equal‐absorbance solutions. A computational study has shown that 5‐methylation of Cyt does not alter the tautomeric distribution in the gas phase or in solution (29), suggesting once again that ribosyl substitution increases the electronic transition moment of the S 1 → S N transition.…”
Section: Resultsmentioning
confidence: 99%
“…However, the tautomeric equilibria between the forms can be influenced by the presence of different substituents. Many theoretical studies on the effect of substituents on the stability of cytosine [39][40][41], 2-pyridones [42], and 5-halogenuracils [43,44], have been reported. 1,3-Dimethyluracil 410.5 ± 0.9 [32] 96.9 ± 1.2 [32] 313.6 ± 1.5 [32] The thermodynamic experimental data presented here can be very useful, together with theoretical calculations, on the determination of the tautomeric form of the compounds studied that exist in the gas phase.…”
Section: Discussionmentioning
confidence: 99%
“…22 Previous investigations on the tautomers of NABs have included evidence of stabilization of the rare tautomers by substituent groups. 26,27 In these studies the investigated substituents included heavy metals, bromine, and methyl groups. The focus of the present work centers on methylation changes in NABs.…”
Section: Introductionmentioning
confidence: 99%